Understanding the links between positive psychology and fashion: A grounded theory analysis. (1st October 2014) - Masuch, Christoph-Simon; Hefferon, Kate
Fashion is clearly under-represented within contemporary psychology. Amongst the few empirical works that do exist, individual clothing behaviours are frequently dealt with in a context of psychological ill-being. This contradicts earlier psychological writings where clothing practices were thought to be life-affirming and well-being enhancing activities. Against this backdrop, this study explored fashion from a positive psychological perspective. Ten participants reported their subjective experience of day-to-day clothing practices in response to open-ended inquiry. Grounded theory analysis revealed that clothing practices were employed as powerful techniques to negotiate selfhood, befriend the body and manage mood. The interaction of these three processes enabled the management of everyday well-being as fashion was found to be a rich source of positivity in participants' lives. These findings have far-reaching implications for the field of (positive) psychology, opening up a number of doors for potential future research.